(E)‐2‐(1, 3‐Benzothiazol‐2‐yl)‐3‐(4‐fluorophenyl)acrylonitrile: a chain of π‐stacked hydrogen‐bonded rings. (16th May 2013) - Trilleras, Jorge; Velásquez, Kelly; Cobo, Justo; Glidewell, Christopher
<x xml:space="preserve">Abstract</x> The title compound, C16H9FN2S, crystallizes as a nonmerohedral twin with twin rotation about the reciprocal‐lattice vector [10<inline-graphic xlink:href="ark:/27927/pgg3hbw8kvz" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />]*. The molecules are nearly planar and the dihedral angle between the planes of the two aryl rings is only 4.4 (2)°. The molecules are linked by pairs of C—H...N hydrogen bonds to form cyclic centrosymmetric R22(18) dimers, which are linked into chains by an aromatic π–π stacking interaction. Comparisons are made with some related 3‐aryl‐2‐thienylacrylonitriles.